Cloning And Expression Of The Haemagglutininneuraminidase (Hn) Gene From Newcastle Disease Virus (Ndv) Strain Af2240 In Baculovirus (Acmnpv) - Alan, Ong Han Kiat (1999)

(untitled)
Newcastle disease virus strain AF2240 is a major threat to the poultry industry as it causes 100% mortality to susceptible flocks The haemagglutininneuraminidase (HN) gene encodes for the HN surface glycoprotein which is known for virus attachment and contains immunogenic properties Therefore, the HN gene was cloned into a Baculovirus Expression Vector system (BEVS) for the development of a subunit vaccine against NDV as well as to study its expression in isolation from the other NDV structural genes The approach taken involved the amplification (RT-PCR) of the I8 kb HN gene, from NDV strain AF2240 genomic RNA and cloning it into a BEVS The